IMPLEMENTASI LAYANAN PUBLIK BERBASIS SMART GOVERNANCE: STUDI KASUS PROGRAM GEULIS DI KOTA BANDUNG - Allyah Nur Rahmani; Dhinda Dwi Maharani; Najwa Auliya Syarifah; Ivan Darmawan (Cahaya Ilmu Bangsa, 2024)
Public service is a duty of the government and its apparatus to fulfill the basic needs of its citizens who have fulfilled their obligations as citizens. Thus, public service from the perspective of citizens is a